Comprehensive Analysis of Cuproptosis-Related Genes in Immune Infiltration and Prognosis in Melanoma - Lv, Haozhen; Liu, Xiao; Zeng, Xuanhao; Liu, Yating; Zhang, Canjing; Zhang, Qi; Xu, Jinhua (Frontiers in Pharmacology, 2022)
Skin cutaneous melanoma(SKCM, hereafter refer to melanoma) is the most lethal skin cancer with increasing incidence. Regulated cell death plays an important role in tumorigenesis and serves as an important target for almost all treatment strategies. Cuproptosis is the most recently identified copper-dependent regulated cell death form that rely on mitochondria respiration. However, it’s role in tumorigenesis remains unknown. The correlation of cuproptosis related genes with tumor prognosis is far to be understood, either. In our present study, we explored the correlation between cuproptosis related genes with the prognosis of melanoma through accessing and analysis of public database, and found 11 out 12 genes were upregulated in melanoma tissues and 3 genes (LIPT1, PDHA1, SLC31A1) have predictive value for the prognosis. Subgroup of melanoma patients with higher cuproptosis related gene expression showed longer overall survival than those with lower gene expression. We chose LIPT1 for further exploration. LIPT1 expression was increased in melanoma biopsies and was an independent favorable prognostic indicator for melanoma patients. Moreover, LIPT1 expression was positively correlated with PD-L1 expression and negatively associated with Treg cell infiltration. The melanoma patients with higher LIPT1 expression showed longer overall survival than those with lower LIPT1 expression after receiving immunotherapy, indicating the prognostic predictive value of LIPT1. Finally, a pan-cancer analysis indicated that LIPT1 was differentially expressed in diverse cancers as compared to normal tissues and correlated with the expression of multiple immune checkpoints, especially PD-L1. It could serve as a favorable prognosis indicator in some cancer types. In conclusion, our study demonstrated the prognostic value of cuproptosis related genes, especially LIPT1, in melanoma, and revealing the correlation between LIPT1 expression and immune infiltration in melanoma, thus providing new clues on the prognostic assessment of melanoma patients and providing a new target for the immunotherapy of melanoma.